Infectious Diseases in the Pediatric Intensive Care Unit - Nadel, Simon (Springer London : Imprint: Springer, 2008)
Many children are admitted to a pediatric intensive care unit (PICU) with serious infections or with a high chance of acquiring nosocomial infection once admitted. Any infection can be serious in an immunocompromised patient, while any delay in therapy may produce more severe infection in an immunocompetent patient. The increasing numbers of PICU admissions mean that knowledge of pediatric infections is vitally important for all involved to enable them to understand the reasons for admission, risks of nosocomial infection, infection control, modes of therapy, and outcomes. Infectious Diseases in the Pediatric Intensive Care Unit has brought together all the current knowledge in the diagnosis and management of infectious disease on the PICU. Taking a practical and evidence-based approach, the editor and his renowned team of contributors provide a comprehensive clinical review of the subject in one easily accessible reference work from neonatal to adolescent and immunocompromised toimmunocompetent. It is therefore relevant to all clinicians working in intensive care, including pediatricians, PICU clinicians, emergency physicians, anesthetists, adult intensivists and nursing and care-based staff.